EFEKTIFITAS MEDIA PEMBELAJARAN GAME MATH FOR KIDS TERHADAP KEMAMPUAN NUMERASI SISWA KELAS V SD NEGERI 013 RAMBAH - Pratama, Amthorie Bangkit; Chandra, Detri Amelia; Dwiana, Ari Aprilia; Muslim, Muslim (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract:This study aims to examine the effectiveness of the Game Math for Kids learning media in improving the numeracy skills of fifth-grade students at SD Negeri 013 Rambah. The research employed an experimental method with a One Group Pretest-Posttest design involving 24 students as participants. The instrument used was a set of pretest and posttest assessments designed to measure students’ numeracy abilities before and after the treatment. Data analysis revealed an increase in the average score from 58.88 (pretest) to 74.04 (posttest). The paired sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. The calculated N-Gain score was 0.369, which falls into the moderate effectiveness category. Furthermore, the effect size measured by Cohen’s d was 2.06, indicatinga very large effect. Therefore, the use of Game Math for Kids is proven to be effective in significantly and meaningfully enhancing elementary school students’ numeracy skills. Keyword:GameMathfor Kids, numeracyskills, learning media, N-Gain, Cohen’s d.  Abstrak:Penelitian ini bertujuan untuk menguji efektivitas media pembelajaran GameMathfor Kids terhadap peningkatan kemampuan numerasi siswa kelas V SD Negeri 013 Rambah. Penelitian ini menggunakan metode eksperimen dengan desain One Group Pretest-Posttest, yang melibatkan 24 siswa sebagai subjek penelitian. Instrumen yang digunakan berupa tes pretest dan posttest yang dirancang untuk mengukur kemampuan numerasi siswa sebelum dan sesudah perlakuan. Hasil analisis data menunjukkan bahwa terdapat peningkatan skor rata-rata dari 58,88 pada pretest menjadi 74,04 pada posttest. Uji pairedsample t-test menunjukkan nilai signifikansi sebesar 0,000 (< 0,05), yang berarti terdapat perbedaan yang signifikan antara skor pretest dan posttest. Nilai N-Gain yang diperoleh sebesar 0,369 menunjukkan kategori efektivitas sedang. Sementara itu, perhitungan effectsize dengan menggunakan Cohen’s d menghasilkan nilai sebesar 2,06 yang termasuk kategori efek sangat besar. Dengan demikian, penggunaan GameMathfor Kids terbukti efektif dalam meningkatkan kemampuan numerasi siswa sekolah dasar secara signifikan dan bermakna.  Kata kunci:GameMathfor Kids, kemampuan numerasi, media pembelajaran, N-Gain, Cohen’s d.